2018
DOI: 10.14202/vetworld.2018.834-839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meniran (Phyllanthus niruri L.) administration on leukocyte profile of broiler chickens infected with Mycoplasma gallisepticum

Abstract: Aim:This study aimed to evaluate the effects of Meniran extract (Phyllanthus niruri L.) administration on leukocyte profile of broiler chickens infected with Mycoplasma gallisepticum.Materials and Methods:Thirty broiler chickens, 21 days old were divided into five treatment groups. P0 (−): Chickens without any treatment; P0 (+), P1, P2, and P3: Chickens were infected with M. gallisepticum 108 cells/ml/animal orally, then given no treatment, Meniran extract 60%, 62.5%, and 65% orally at a dose of 1 ml/kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 30 publications
1
18
0
3
Order By: Relevance
“…In this experiment, it was difficult to relate the MCH levels to FERM as the MCH levels were not linearly dependent on dietary FERM levels. Heterophils is leukocytes fraction that have been attributed to the defence against bacteria that may jeopardize the chickens, and that the increased heterophils counts may indicate the bacterial infections/inflammation in chickens (Hidanah et al, 2018). In this current work, ANOVA test showed that dietary inclusion of FERM significantly influenced the counts of heterophils in the circulatory system of chickens.…”
Section: Discussionsupporting
confidence: 48%
“…In this experiment, it was difficult to relate the MCH levels to FERM as the MCH levels were not linearly dependent on dietary FERM levels. Heterophils is leukocytes fraction that have been attributed to the defence against bacteria that may jeopardize the chickens, and that the increased heterophils counts may indicate the bacterial infections/inflammation in chickens (Hidanah et al, 2018). In this current work, ANOVA test showed that dietary inclusion of FERM significantly influenced the counts of heterophils in the circulatory system of chickens.…”
Section: Discussionsupporting
confidence: 48%
“…Our inference was also supported by the reduced levels of leukocytes and lymphocytes in the blood of broilers. Note that the increase in leukocytes and lymphocytes levels may indicate the infections and inflammation in broiler chickens (Hidanah et al, 2018). It was most likely that organic acids and lactic acid bacteria in the fermented A. bilimbi L. filtrate acted as antibacterial agents in the intestine of broilers in the present study.…”
Section: Discussionmentioning
confidence: 59%
“…It was clear that chickens in the BACI and FERM groups had lower (p<0.05) leukocytes and lymphocytes numbers as compared particularly to the chickens in CONT group. A former study by Hidanah et al [21] noticed the increased leukocytes and lymphocytes numbers following Mycoplasma gallisepticum infection. Similarly, Akhtar et al [22] reported that infection with mixed Eimeria species increased the numbers of leukocytes and lymphocytes in broiler chickens.…”
Section: Resultsmentioning
confidence: 95%